2010
DOI: 10.1038/jhh.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypertension in rural Cambodia: results from a 6-year programme

Abstract: This study was aimed to describe the outcomes of a hypertension treatment programme in two outpatient clinics in Cambodia. We determined proportions of patients who met the optimal targets for blood pressure (BP) control and assessed the evolution of mean systolic and diastolic BP (SBP/DBP) over time. Multivariate analyses were used to identify predictors of BP decrease and risk factors for LTFU. A total of 2858 patients were enrolled between March 2002 and June 2008 of whom 69.2% were female, 30.5% were aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…; Isaakidis et al . ). While we do not have data to substantiate our speculation, the high rate of LTFU in Kibera is likely to be a reflection of (i) the highly transient population of Kibera and the competing interests of work and survival in such a setting, and (ii) lack of awareness of the disease(s) coupled with lack of adherence to treatment in the long run.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Isaakidis et al . ). While we do not have data to substantiate our speculation, the high rate of LTFU in Kibera is likely to be a reflection of (i) the highly transient population of Kibera and the competing interests of work and survival in such a setting, and (ii) lack of awareness of the disease(s) coupled with lack of adherence to treatment in the long run.…”
Section: Discussionmentioning
confidence: 97%
“…; Isaakidis et al . ). In these studies, the model of care was based on a specialised HIV/Chronic Diseases clinic model and not on a primary care approach.…”
Section: Introductionmentioning
confidence: 97%
“…In practice, care outside of the national hospitals in the capital and the provincial hospitals is limited. Some private-not-for-profit hospitals have launched diabetes care projects, but these proved difficult to sustain without external support [ 23 , 24 ]. In urban areas, the private health sector has grown steadily and many small-scale health service providers, especially lower echelon providers, get most of their revenues through selling pharmaceuticals.…”
Section: Methodsmentioning
confidence: 99%
“…With recent evidence highlighting the prevalence of hypertension and related metabolic disorders in Cambodia,1 2 attention is now being given to initiating evidence-based prevention and control strategies. A national survey in 2010 revealed that hypertension had an urban prevalence of approximately 16.90%, a rural prevalence of 10.00%, and overall country prevalence of 11.20% among persons aged 25–64 years 3…”
Section: Introductionmentioning
confidence: 99%